Respuesta :

ncsftw

Answer:

P(-6) = 4 P(6) = -6

Step-by-step explanation:

above

The two evaluations of the given polynomial are:

P(-6) = -36

P(-6) = -36

How to find the evaluations of P(x)?

Here we know that:

P(x)/(x - 6) = Q(x)

So we can rewrite:

P(x) = Q(x)*(x - 6).

Now, first we want to get two evaluations, the first one is P(-6), here we do know that Q(-6) = 3, so:

P(-6) = Q(-6)*(-6 - 6) = 3*-12

P(-6) = -36

Now we want to get P(6), so we have:

P(6) = Q(6)*(6 - 6) = Q(6)*0 = 0

P(6) =  0.

So the two evaluations are:

P(-6) = -36

P(-6) = -36

If you want to learn more about polynomials, you can read:

https://brainly.com/question/4142886

#SPJ2